2010
DOI: 10.1143/apex.3.032103
|View full text |Cite
|
Sign up to set email alerts
|

High Extraction Efficiency GaN-Based Photonic-Crystal Light-Emitting Diodes: Comparison of Extraction Lengths between Surface and Embedded Photonic Crystals

Abstract: This work presents the experimental measurement of the extraction lengths of individual guided modes of embedded photonic-crystal (PhC) lightemitting diodes (LEDs), which corroborates its superior guided light extraction compared to surface PhC LEDs. While in surface PhC LEDs a number of low order modes were not observed experimentally, in embedded PhC LEDs, the stronger interaction of all guided modes with the PhCs resulted in the diffraction of all low order modes with short extraction lengths, ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…To effectively extract the guided light in the rather thick free-standing m-plane GaN substrates, the PhCs were placed within the LED structure, which increases their interaction with the guided modes (schematics in Figure 2a). 25 An improved diffraction efficiency is obtained by embedding air gaps within the GaN, which results in a large contrast in refractive index. The extraction of polarized light by embedded PhCs in m-plane GaN LEDs was further motivated by the high extraction efficiency previously observed in c-plane GaN LEDs.…”
Section: 24mentioning
confidence: 99%
“…To effectively extract the guided light in the rather thick free-standing m-plane GaN substrates, the PhCs were placed within the LED structure, which increases their interaction with the guided modes (schematics in Figure 2a). 25 An improved diffraction efficiency is obtained by embedding air gaps within the GaN, which results in a large contrast in refractive index. The extraction of polarized light by embedded PhCs in m-plane GaN LEDs was further motivated by the high extraction efficiency previously observed in c-plane GaN LEDs.…”
Section: 24mentioning
confidence: 99%
“…The measured extraction length for four diffraction vectors of fundamental guided modes is 109 lm (2G CX ), 93 lm (G X1M ), 123 lm (G CM ), and 122 lm (2G CM ), respectively, which matches the previous literature results. 15 These experimental determinations of the PhC extraction length indicated that the minimum device emission area of the GaN PhC l-uTFLED must be more than 1E4 square microns, which allows for extraction of all guided light. Through this analysis, the diffracted angle h out of the guided mode extraction characteristics from the GaN PhC l-uTFLEDs can be studied further when the PhC emission aperture sizes are less the 1E4 square microns.…”
mentioning
confidence: 94%
“…12,15 The linewidth of each diffracted guided mode is related to its extraction length, which serves as a probe of PhC modal extraction, as shown in Fig. 2.…”
mentioning
confidence: 99%
“…An initial demonstration of bio-inspired compound eye structures (CESs) on GaP-based red LEDs showed excellent performance for light extraction efficiency [8]. Previously, the large indexcontrast embedded photonic crystals [9], [10], self-assembled colloidal MLAs [11], [12], [14], and concave microstructure arrays via imprinting methods [13] had been used for achieving improved light extraction over a large angular distribution, which in turn resulted in significant increase in light extraction efficiency in GaN-based LEDs (GaN LEDs). Similar concept by using colloidal MLAs had also been used for efficient extraction of both guided mode and substrate mode in organic LED [14].…”
Section: Introductionmentioning
confidence: 99%